Role of N6-Methyladenosine Methylation Regulators in the Drug Therapy of Digestive System Tumours - Xia, Zhelin; Kong, Fanhua; Wang, Kunpeng; Zhang, Xin (Frontiers in Pharmacology, 2022)
Digestive system tumours, including stomach, colon, esophagus, liver and pancreatic tumours, are serious diseases affecting human health. Although surgical treatment and postoperative chemoradiotherapy effectively improve patient survival, current diagnostic and therapeutic strategies for digestive system tumours lack sensitivity and specificity. Moreover, the tumour’s tolerance to drug therapy is enhanced owing to tumour cell heterogeneity. Thus, primary or acquired treatment resistance is currently the main hindrance to chemotherapy efficiency. N6-methyladenosine (m6A) has various biological functions in RNA modification. m6A modification, a key regulator of transcription expression, regulates RNA metabolism and biological processes through the interaction of m6A methyltransferase (“writers”) and demethylase (“erasers”) with the binding protein decoding m6A methylation (“readers”). Additionally, m6A modification regulates the occurrence and development of tumours and is a potential driving factor of tumour drug resistance. This review systematically summarises the regulatory mechanisms of m6A modification in the drug therapy of digestive system malignancies. Furthermore, it clarifies the related mechanisms and therapeutic prospects of m6A modification in the resistence of digestive system malignancies to drug therapy.